ISQ calculation evaluation of in vitro laser scanning vibrometry-captured resonance frequency - Stijn Debruyne; Nicolas Grognard; Gino Verleye; Korneel Van Massenhove; Dimitrios Mavreas; Bart Vande Vannet (SpringerOpen, 2017)
Abstract Background Implant stability testing at various stages of implant therapy by means of resonance frequency analysis is extensively used. The overall measurement outcome is a function of the resulting stiffness of three entities: surrounding bone, bone-implant complex, and implant-Smartpeg complex. The influence of the latter on the overall measurement results is presently unknown. It can be investigated in vitro by use of imbedded implants with mounted Smartpegs. This enables to keep the influence of the two other entities constant and controlled. The purpose of this study is to verify if a laboratory laser Doppler vibrometry technology-based procedure results in comparable ISQ results after calculation of captured resonance frequency spectra by aid of the Osstell algorithm with direct Osstell IDX device measurements. Methods A laboratory procedure was engineered to record frequency spectra of resin-imbedded test implants with mounted Smartpegs, after electromagnetic excitation with the Osstell IDX device and laser Doppler vibrometry response detection. Fast Fourier transformation data processing of resonance frequency data resulted in determination of a maximum resonance frequency values allowing calculation of implant stability quotient (ISQ) values using the Osstell algorithm. Results Laboratory-based ISQ values were compared to Osstell IDx device-generated ISQ values for Straumann tissue level, Ankylos, and 3i Certain implant systems. For both systems, a correlation coefficient r = 0.99 was found. Furthermore, a clinically rejectable mean difference of 0.09 ISQ units was noted between both datasets. Conclusions The proposed laboratory method with the application of the Osstell algorithm for ISQ calculation is appropriate for future studies to in vitro research aspects of resonance frequency analysis implant stability measurements.